Phytochemical studies and in vitro, in vivo and in silico antidiabetic activities of Paederia foetida L. extract - Tan, Dai Chuan (2021)
Paederia foetida L. (Rubiaceae) is an edible plant distributed in Asian countries including Malaysia. Fresh leaves have been traditionally used to treat various diseases, including diabetes and as a remedy for indigestion and diarrhea. The plant has reported as antioxidant and antidiabetic properties. The plant is known as rich source of alkaloids, flavonoids, phenols, terpenoids etc. However, the bioactive compounds and the mechanisms of their beneficial effects have remained largely unknown particularly on the twig part of the plant. Therefore, the study covered the investigation of the enzyme inhibition ( -amylase, -glucosidase, and dipeptidyl peptidase-4) of Paederia foetida twig extracts by in vitro assays, the identification of the phytoconstituents of Paederia foetida twigs, evaluation of the antidiabetic activity of Paederia foetida using high fat diet-low dose streptozotocin-induced Sprague Dawley rats model, and performance of in silico molecular docking of identified bioactive compounds. The chloroform extract showed the lowest in vitro -amylase (9.60 μg/mL), -glucosidase (245.6 μg/mL), and dipeptidyl peptidase-4 (DPP-4) (67.40%) inhibition activities compared to other extracts. -amylase -glucosidase inhibitory activity of the isolated compound, scopoletin had IC50 values of 0.052 and 0.057 mM, respectively. The chloroform extract also showed the highest total phenolic content among all the extracts. For the identification of antidiabetic compounds or enzyme inhibitors, assay guided isolation and metabolomics techniques were applied. Assay guided isolation technique revealed the chloroform extract as the most active extract and further purification afforded scopoletin as a bioactive antidiabetic compound. Meanwhile loading column scatter plot of orthogonal partial least square (OPLS) model in Gas Chromatography-Mass Spectrometry (GC-MS) metabolomics revealed the presence of 12 antidiabetic compounds, namely, dl- -tocopherol, n-hexadecanoic acid, 2-hexyl-1-decanol, stigmastanol, 2-nonadecanone, cholest-8(14)-en-3-ol,4,4-dimethyl-,(3 ,5 )-, stigmast- 4-en-3-one, stigmasterol, 1-ethyl-1-tetradecyloxy-1-silacyclohexane, -sitosterol, stigmast-7-en-3-ol, (3 ,5 ,24S)-, and -monostearin. For proton Nuclear Magnetic Resonance (1H-NMR) metabolomics, the chloroform extract showed the presence of 13 antidiabetic compounds, campesterol, - -terpineol, lupeol, epifriedelinol, embelin, scopoletin, rutin, apigenin, geniposide, and linarin. The standardization of the chloroform extract was carried out to identify the exact amount of the biomarker derived from the plant. The qNMR is a powerful analytical tool for the rapid and accurate determination of bioactive ingredients in herbal preparation. The validated qNMR method showed a good linearity (r2 = 0.9999), limit of detection (0.009 mg/mL), and quantification (0.029 mg/mL), together with high stability (relative standard deviation = 0.022%), high precision (RSD < 1%), and good recovery (94.08%- 108.45%). The P. foetida chloroform extract showed 7.34% scopoletin content, while the other extracts did not show any scopoletin content. The standardized extract was further evaluated for in vivo antidiabetic study at doses of 50 (Group 4) and 100 (Group 5) mg/kg and compared with 300 mg/kg metformin (Group 6). The in vivo results indicated that P. foetida extract of 50 mg/kg displayed the management of metabolic disorders of diabetic rats toward the normal state. The normal and obese rats displayed normal range of blood glucose levels while higher levels in diabetic rats. Groups 4, 5, and 6 showed significant decrement of blood glucose levels compared to diabetic rats (Group 3). There was 27.19% reduction of blood glucose level in Group 4 followed by 23.14% in Group 6 and then 16.79% in Group 5. Group 4 improved lipid profile, renal, and liver function as compared to Group 5 and 6. Group 4 showed reduction in the serum total cholesterol, triglycerides, low-density lipoproteins, uric acid, AST, and ALP and increase in high-density lipoprotein and total protein. Besides that, Group 4 exhibited good antioxidant activities in catalase (25.96 U/mg protein) and glutathione peroxidase (17.62 nmol/mg protein) analysis in the liver tissues, respectively. Group 4 also able to reduce the oxidative stress in protein carbonyl content and receptor for advanced glycation end-product markers. Molecular docking study was attempted to elucidate the mechanisms by which the active compounds could induce antidiabetic activities in - amylase, -glucosidase, and DPP-4. In silico calculations gave binding energy between scopoletin -amylase, -glucosidase, and DPP-4 of -6.03, -2.92, and -6.1 kcal/mol, respectively. A total of two hydrogen bonds (Glu171 and Gly139) were observed in scopoletin- -amylase complex along with one hydrophobic interaction (Ala169). The scopoletin- -glucosidase complex showed two hydrogen bonding (Arg450 and Gln439) and one hydrophobic interaction (Tyr41). Besides that, one hydrogen atom in scopoletin showed a carbon-hydrogen bond to Ser360 in the DPP-4 enzyme. In conclusion, P. foetida exhibited enzyme inhibition in vitro and improved glucose and biochemical parameters in diabetic rats. This study suggested the potential of P. foetida as health promoting agent for Type 2 Diabetes Mellitus.